2019
DOI: 10.1515/dx-2018-0073
|View full text |Cite
|
Sign up to set email alerts
|

Understanding diagnosis through ACTion: evaluation of a point-of-care checklist for junior emergency medical residents

Abstract: Background Avoiding or correcting a diagnostic error first requires identification of an error and perhaps deciding to revise a diagnosis, but little is known about the factors that lead to revision. Three aspects of reflective practice, seeking Alternative explanations, exploring the Consequences of missing these alternative diagnoses, identifying Traits that may contradict the provisional diagnosis, were incorporated into a three-point diagnostic checklist (abbreviated to ACT). Methods Seventeen first and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Sibbald’s cardiac exam checklist reported 51% accuracy with checklist use vs 46% diagnostic accuracy without (p=0.04)52; and Shimizu’s symptom-specific checklists reported 67% diagnostic accuracy with the checklist vs 60% without (p<0.05) 57. One study (Kilian’s ACT mnemonic) reported no significant improvements in postchecklist diagnostic accuracy 62…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Sibbald’s cardiac exam checklist reported 51% accuracy with checklist use vs 46% diagnostic accuracy without (p=0.04)52; and Shimizu’s symptom-specific checklists reported 67% diagnostic accuracy with the checklist vs 60% without (p<0.05) 57. One study (Kilian’s ACT mnemonic) reported no significant improvements in postchecklist diagnostic accuracy 62…”
Section: Resultsmentioning
confidence: 98%
“… 57 One study (Kilian’s ACT mnemonic) reported no significant improvements in postchecklist diagnostic accuracy. 62 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of mistakes in the diagnosis are caused by cognitive errors [ 6 ], and besides educational strategies, checklists have successfully been implemented in medicine to reduce errors and increase treatment quality [ 7 ], e.g., reducing central line infection rates [ 8 ] and surgical complications [ 9 ]. Diagnostic decision support systems (DDSS) and symptom checkers (SCs) are increasingly used [ 10 12 ] and promise to help patients and healthcare professionals to establish the correct diagnosis by providing a checklist of differential diagnoses [ 13 ].…”
Section: Introductionmentioning
confidence: 99%